FarmUSE: Assessment of antimicrobial use in poultry farms - Muloi, Dishon M.; Ibayi, Eugine L.; Murphy, Mike; Njaramba, Jane K.; Nielsen, S.S.; Hoffmann, Vivian; Moodley, Arshnee (International Livestock Research Institute, 2024)
Antimicrobial use in livestock systems is thought to be a key driver for the development of antimicrobial resistance (AMR). Therefore, efforts to reduce antimicrobial use are seen as a key intervention to controlling AMR. Understanding the patterns of antimicrobial use in different production systems is essential. Antimicrobials are commonly used in poultry production for disease treatment, prevention and, to an extent, growth promotion. In low- and middle-income countries, surveillance of antimicrobial use in animals is hampered by the lack of standardised data collection tools and reporting systems across different countries and regions. To address this gap, these tools were developed and adapted to poultry broiler production systems to support the collection of comprehensive data related to demographics, production and antibiotic usage data. The tools are designed for both retrospective and prospective data gathering.